Gambaran Model Penyelesaian Ketidakpuasan Pelayanan Kesehatan BPJS (Studi Kasus Pelayanan BPJS Di Rumah Sakit Umum Yogyakarta) - Santoso Putri, Filu Marwati; , Prof. Dr. Harun Joko Prayitno, M.Hum; , Dr. Nurhadiantomo (2015)
Act No. 24 of 2011 sets, the National Social Security will be held by BPJS. To improve the health of society, including the poor, the few hospitals that have collaborated with BPJS BPJS willing to serve patients in accordance with the provisions set out in Law No. 40 of 2004 on the National Security System. As far as the field for this in a number of health centers and hospitals, BPJS implementation is still in shambles. The whole place became flooded patient health care and create long lines. Even more alarming, some participants found BPJS, which previously was relocated from Askes civil servants earn less than the maximum service. Another fact that needs to be highlighted is about the availability of drugs in hospitals BPJS organizers. Had been a case in which the hospital only tell part of the prescription drugs that are made by physicians, while the remaining medication must be purchased in private pharmacies. Some of the above phenomena indirectly illustrates that the implementation is not yet fully BPJS nice and still reap some problems. This research is a juridical empirical research approach consisting of a descriptive approach, an explanatory and prescriptive. Methods of data collection consisted of a literature and documentation, observation and interviews. Methods of data analysis is the method of qualitative analysis . The results of this study indicate that the implementation of health care patients BPJS still reap some of the disputes that need to be presented in the framework of a model of settling the dispute.